BURNOUT SYNDROME IN PHYSICIANS OF A HOSPITAL IN THE PERUVIAN AMAZON: SÍNDROME DE BURNOUT EN MÉDICOS DE UN HOSPITAL DE LA AMAZONÍA PERUANA - Vilchez-Cornejo, Jennifer (2019)
Objective: To determine Burnout Syndrome (SBO) in physicians treated in the outpatients clinic of a hospital in the Peruvian Amazon during 2017. Methods: Analytical cross-sectional study; which included 30 medical surgeons who attended in the external offices of the specialties of Internal Medicine, General Gynecology and Pediatric Surgery of the Regional Hospital of Pucallpa, professional exhaustion was determined through the Maslach Burnout Inventory (MBI) and the perception of the patient-doctor relationship using the scale (PREMEPA). Generalized linear models were performed by prevalence ratios crude and adjusted estimated with a 95% confidence interval. Results: 76.7% of the doctors were male, eight out of ten suffered Burnout. 20% of the patients were satisfied and only 16.7% indicated they had a median physician-patient medical relationship. Statistically significant association was found among those suffering from Burnout and theoutpatient offices were treated of surgery services (RPa: 1.46; 95% CI: 1.20–1.76), obstetric gynecology (RPa: 1.69; 95% CI: 1.41–2.03) or in those patients who were dissatisfied with the consultation provided (RPa: 1.59; 95% CI: 1.22-2.07), having medical residency was a protective factor to develop Burnout (RPa: 0.62; 95% CI: 0.62– 0.77). Conclusion: Patients claim to have adequate levels of physician-patient relationship despite the high rate of doctors suffering from Burnout, surgical specialties predispose doctors to develop Burnout. However, having performed medical residency predisposed the doctor to have less Burnout Syndrome.